Ruptured Renal Artery Aneurysm in a Young Man with Uncontrolled Hypertension - Sekarini, Ajeng Ayu; Sukesi, Lilik; Supriyadi, Rudi (Indonesian Journal of Kidney and Hypertension, 2026)
Renal artery aneurysm (RAA) is a rare renovascular condition that may represent both a consequence of long-standing hypertension and an underrecognized cause of secondary hypertension, particularly in young patients. A 23-year-old man with a four-year history of poorly controlled hypertension (peak blood pressure 170/100 mmHg) presented with acute left flank pain. On admission, blood pressure was 154/110 mmHg with severe anemia (hemoglobin 6.3 g/dL), preserved renal function (creatinine 1.18 mg/dL), and mild proteinuria (1+) without hematuria. Contrast-enhanced CT angiography demonstrated a 2.54-cm saccular RAA (Rundback type I) arising from the left renal artery, accompanied by a large perirenal hematoma measuring 8.3 × 6.7 × 14.2 cm, consistent with rupture. The patient had been taking intermittent captopril 12.5 mg once daily prior to admission. Selective endovascular coil embolization using a 3.3-mm VortX coil via right femoral access was successfully performed, achieving complete aneurysm exclusion with preserved renal perfusion. This case highlights the bidirectional relationship between hypertension and RAA. Chronic hypertension likely contributed to aneurysm formation, while intrarenal hemodynamic disturbances may have activated the renin-angiotensin-aldosterone system (RAAS), leading to secondary hypertension. The marked improvement in blood pressure following intervention supports a reversible renovascular mechanism. RAA should be considered in young patients with uncontrolled or resistant hypertension. Early vascular imaging and timely endovascular management are essential to prevent life-threatening complications and address reversible renovascular hypertension.